1988
DOI: 10.1126/science.2974179
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP-Responsive DNA-Binding Protein: Structure Based on a Cloned Placental cDNA

Abstract: Cyclic AMP (cAMP) is an intracellular second messenger that activates transcription of many cellular genes. A palindromic consensus DNA sequence, TGACGTCA, functions as a cAMP-responsive transcriptional enhancer (CRE). The CRE binds a cellular protein of 38 kD in placental JEG-3 cells. A placental lambda gt11 library was screened for expression of specific CRE-binding proteins with the CRE sequence as a radioactive probe. A cDNA encoding a protein of 326 amino acids with the binding properties of a specific CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
350
1
2

Year Published

1990
1990
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 731 publications
(359 citation statements)
references
References 30 publications
6
350
1
2
Order By: Relevance
“…pmTF-1 (1.5 kb EcoRl fragment) and pmTF-2 (750 bp EcoRl fragment) are subclones of the full-length mouse transferrin cDNA (S. R.. unpublished data), which have been identified by revealing more than 86% sequence homology to the human transferrin gene (Yang et al, 1984). pmcCREB61 (S. R., unpublished data) contains a 1.2 kb EcoRl fragment corresponding to the mouse cDNA encoding the CREB isolated by cross-hybridization with the human CREB cDNA clone (Hoeffler et al, 1988). pSP-GAPDH contains the 800 bp Xbal-Pstl fragment of pRGAPDH-13 (Fort et al, 1985) cloned into the pSP64 vector (W. S., unpublished data).…”
Section: Constructionmentioning
confidence: 99%
“…pmTF-1 (1.5 kb EcoRl fragment) and pmTF-2 (750 bp EcoRl fragment) are subclones of the full-length mouse transferrin cDNA (S. R.. unpublished data), which have been identified by revealing more than 86% sequence homology to the human transferrin gene (Yang et al, 1984). pmcCREB61 (S. R., unpublished data) contains a 1.2 kb EcoRl fragment corresponding to the mouse cDNA encoding the CREB isolated by cross-hybridization with the human CREB cDNA clone (Hoeffler et al, 1988). pSP-GAPDH contains the 800 bp Xbal-Pstl fragment of pRGAPDH-13 (Fort et al, 1985) cloned into the pSP64 vector (W. S., unpublished data).…”
Section: Constructionmentioning
confidence: 99%
“…Originally identi®ed for the signal transduction of nuclear e ects of PKA activation (Hoe er et al, 1988;Gonzalez et al, 1989), the cyclic AMP response element binding (CREB) protein is a basic/leucine zipper (B-ZIP) transcription factor that functions in vivo to regulate the proliferation of pituitary cells (Struthers et al, 1991) and thymocytes (Barton et al, 1996) and contributes to the establishment of circadian rhythms (Foulkes et al, 1996). The CREB family (de®ned by cross-dimerization and homology in the basic and leucine zipper domains) consists of multiple isoforms of CREB, multiple isoforms of the cyclic AMP-response element protein modulator (CREM), and Activating Transcription Factor (ATF)-1.…”
Section: Introductionmentioning
confidence: 99%
“…The transcriptional activator CREB was the ®rst member of this class to be described (Hoe er et al, 1988). It has been found that CREB function is tightly regulated by phosphorylation (Yamamoto et al, 1988).…”
Section: Introductionmentioning
confidence: 99%